Lado English Series : book 5 - Lado, Robert (New York : Regents Publishing Company, 1980)
Contiene: Deciding between work and entertainment. Lost and found. Solving a crime. An emergency decision. Refusing an invitation. Friday the thirteenth. Volunteer work. Choosing a career. Honesty or loyalty. Getting admitted to a good university